ChemInform Abstract: Reaction of Benzyne with Fluorinated 1, 3‐Dicarbonyl Compounds. Issue 25 (3rd June 2013) - Zahid, Muhammad; Ibad, Muhammad Farooq; Abilov, Zharylkasyn A.; Langer, Peter
Abstract Various fluorinated 1, 5‐dicarbonyl compounds (III) are regioselectively obtained by the insertion of fluorinated 1, 3‐dicarbonyl compounds (II) to benzyne.